Banks fearing the drought? Liquidity hoarding as a response to idiosyncratic interbank funding dry-ups - Helge Littke; Matias Ossandon Busch (Deutsche Bundesbank, 2021)
We investigate whether idiosyncratic interbank funding shocks affecting a bank headquarters can trigger a liquidity hoarding reaction by their regional branches. Shock-affected branches of Brazilian banks increase liquid assets and cut lending in the shocks' aftermath compared to non-affected branches within the same municipality, even in absence of a market-wide freeze. These effects increase in branches' reliance on internal funding and vary depending on banks' access to central bank emergency liquidity. Our findings suggest that the geographical fragmentation of branches' funding limits their ability to offset idiosyncratic funding shocks.
Keywords: G01; G11; G21; 330; Interbank funding; Internal capital markets; Financial market structure; Liquidity risk; Central bank interventions